2019
DOI: 10.1155/2019/5698460
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Compression Tights on Recovery Parameters after Exercise Induced Muscle Damage: A Randomized Controlled Crossover Study

Abstract: Introduction Recent meta-analyses on compression garments have reported faster recovery of muscle function particularly after intense eccentric power or resistance exercise. However, due to the complex interaction between cohorts included, exercises involved and compression applied, recovery length and modalities, and outcome parameters selected, only limited practical recommendations can be drawn from these studies. Thus, our aim was to determine the effect of compression tights on recovery from high mechanic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 42 publications
1
20
0
4
Order By: Relevance
“…The same authors found compression to be most effective for improving recovery from exercise that elicits a large degree of muscle damage (30); just as demonstrated in our study. Recovery from resistance or plyometric exercise has been demonstrated to derive the greatest bene ts from compression (30,31). Indeed, the wide range in exercise designs, including differences in timing, contraction forms, and intensity, has contributed to apparently inconsistent ndings; thus, speci c recommendations for the ideal exercise regime supporting the use of compression have not yet been elucidated (11).…”
Section: Discussionmentioning
confidence: 99%
“…The same authors found compression to be most effective for improving recovery from exercise that elicits a large degree of muscle damage (30); just as demonstrated in our study. Recovery from resistance or plyometric exercise has been demonstrated to derive the greatest bene ts from compression (30,31). Indeed, the wide range in exercise designs, including differences in timing, contraction forms, and intensity, has contributed to apparently inconsistent ndings; thus, speci c recommendations for the ideal exercise regime supporting the use of compression have not yet been elucidated (11).…”
Section: Discussionmentioning
confidence: 99%
“…The same authors found compression to be most effective for improving recovery from exercise that elicits a large degree of muscle damage [ 28 ]; just as demonstrated in our study. Recovery from resistance or plyometric exercise has been demonstrated to derive the greatest benefits from compression [ 28 , 29 ]. Indeed, the wide range in exercise designs, including differences in timing, contraction forms, and intensity, has contributed to apparently inconsistent findings; thus, specific recommendations for the ideal exercise regime supporting the use of compression have not yet been elucidated [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Die Autoren berichten von signifikanten Zwischengruppenunterschieden für CK und Myoglobin zwischen kombiniertem Protokoll und isolierter Radbelastung mit einer mittleren CK-Konzentration der WB-EMS Variante von über 2000 IE bereits nach 24 h [22]. Eingedenk des Umstandes, dass die Peak CK-Konzentration nach WB-EMS deutlich später auftritt [5,11,12], ist dabei von einem weiteren Ansteigen der CK-Werte in den Bereich einer moderaten Rhabdomyolyse [19] auszugehen. Insofern liegen die von Wahl et al [1] berichteten Daten bei 3-fachem Expositionszeitraum aber lediglich ca.…”
Section: Diskussionunclassified
“…Eine Blutentnahme nach 96 h hätte wichtige Daten über die CK Kinetik (Rückgang/Erhalt/Anstieg) liefern und somit zu Rückschlüssen auf die Regenerationsdauer beitragen können. Aus anderen Studien [5,11] ist zwar bekannt, dass die CK-Konzentration auch nach 96 h im Peak-Bereich verbleibt, allerdings lag die Stimulationsintensität ("Ausbelastung") und die CK-Konzentration (ca. 4fach) dieser Untersuchungen wesentlich höher.…”
Section: Diskussionunclassified
See 1 more Smart Citation